ANALYSIS OF QUALITY IMPROVEMENT AND EMPLOYEE EMPOWERMENT IN EFFORT OF PERFORMANCE IMPROVEMENT ON MANPOWER AND TRANSMIGRATION OFFICE OF KARAWANG REGENCY - Irma Hermayati (Universitas Buana Perjuangan Karawang, 2018)
ABSTRACT The purpose of this study is to analyze and assess the implementation of human resource empowerment, implementation of work programs, inhibiting factors in the empowerment of human resources, inhibiting factors in improving the quality of human resources and efforts to improve performance in the Department of Manpower and Transmigration Karawang regency. This research is expected to contribute to the development of economics especially in the field of management science; As a contribution of scientific literature in the field of human resources management, as reference material in scientific writing, as an information material, both for leaders and employees at the Departemen of Manpower and Transmigration Karawang regency in the implementation of performance-based and career management as well as consideration and input for decision making. The research was conducted by using qualitative method of single case study that is; Collect, present, analyze, triangulate and test the validity of data and make conclusions and suggestions. The focus of research in the field of training and job placement of the Department of Manpower and Transmigration Karawang regency. Unit of research respondents: Head of Department, Head of Division, Secretary of Service, Human Resource Consultant and Human Resources Expert. Based on the results of the analysis, the following conclusions are obtained: the implementation of empowerment of human resources has not been implemented optimally, the implementation of work programs based on routine achievement, the factors that hamper the empowerment of human resources are the factors of human habit and discipline, the inhibiting factors Improving the quality of human resources is a factor of work culture that has formed from the first and efforts to improve performance by holding technical guidance of education and job training in the Department of Manpower and Transmigration Karawang regency. Keywords: empowerment of human resources, performance.